Multinational military forces in the global south: iso-dependence and the quest for autonomy in the security geo-culture - Ferreyra Wachholtz, Matías Daniel Avelino [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
In the post-Cold War era, only three international military organizations with standing headquarters made up exclusively of militaries of states in the Global South have emerged in the field of peace operations. These are the Southern Cross Binational Peace Force in South America, the African Standby Force, integrating five sub-regional African forces, and the Peninsula Shield Force in the command structures of the Gulf Cooperation Council countries. The overall objective of this thesisis to analyze the factors that constrain and promote autonomous practices with multinational military forces in the regions of the Global South in the period 2000-2020. As a research hypothesis, we defend that, in a global field of military crisis management dominated by standards and capitals from central countries, the phenomena of organizational isomorphism and external dependence tend to interweave in the formations of multinational military forces in the Global South. For the analysis, we conceptualize a common condition – iso-dependence – in the peripheral formation of international military organizations. Further, this research uses a typological-comparative framework to analyze the organizational and operational differences between the three mentioned multinational military forces. From historical, critical, and postcolonial studies, we argue that the epistemic autonomy to conduct such force models in the peripheries is constrained in the context of a security geoculture whereby specific attributions, knowledge, and security functions have been unevenly distributed in the modern world-system.

Na era pós-Guerra Fria, apenas três organizações militares internacionais com quartéis-generais permanentes compostos exclusivamente por militares de Estados no Sul Global emergiram no campo das operações de paz. São elas: a Força de Paz Binacional “Cruz del Sur” , na América do Sul, a Força de Reserva Africana, que integra cinco forças sub-regionais africanas, e a Força Escudo da Península entre os países do Conselho de Cooperação do Golfo. O objetivo geral desta pesquisa é analisar os fatores que restringem e promovem práticas autônomas nas forças militares multinacionais no Sul Global no período 2000-2020. Como hipótese de pesquisa, defendemos que, em um campo global de gestão militar de conflitos dominado por padrões e capitais de países centrais, os fenômenos de isomorfismo organizacional e dependência externa tendem a se entrelaçar nas formações de forças militares multinacionais no Sul Global. Para a análise conceituamos uma condição comum – isodependência – na formação periférica de organizações militares internacionais. Além disso, esta pesquisa utiliza um modelo tipológicocomparativo para analisar as diferenças organizacionais e operacionais entre as três organizações militares multinacionais mencionadas. A partir de estudos históricos, críticos e pós-coloniais, argumentamos que a autonomia epistêmica na condução de tais modelos de força nas periferias é restringida no contexto de uma geocultura da segurança pela qual atribuições específicas, conhecimentos e funções de segurança tem sido desigualmente distribuídas no sistema-mundo moderno.

En la era de post-Guerra Fría, solo tres organizaciones militares internacionales con cuarteles generales permanentes compuestos exclusivamente por personal militar de los Estados del Sur Global han emergido en el campo de las operaciones de paz. Estas son: la Fuerza Binacional de Paz “Cruz del Sur”, en Sudamérica, la Fuerza de Reserva Africana, que comprende cinco fuerzas subregionales africanas, y la Fuerza Escudo de la Península entre los países del Consejo de Cooperación del Golfo. El objetivo general de esta investigación es analizar los factores que restringen y promueven prácticas autónomas en las fuerzas militares multinacionales en el Sur Global en el período 2000-2020. Como hipótesis de investigación, sostenemos que, en un campo global de gestión militar de conflictos dominado por estándares y capitales de países centrales, los fenómenos de isomorfismo organizacional y dependencia externa tienden a entrelazarse en la formación de fuerzas militares multinacionales en el Sur Global. Para el análisis conceptualizamos una condición común, la isodependencia, en la formación periférica de las organizaciones militares internacionales. Además, esta investigación utiliza un modelo tipológico-comparativo para analizar las diferencias organizacionales y operacionales entre las tres organizaciones militares multinacionales mencionadas. A partir de estudios históricos, críticos y poscoloniales, sostenemos que la autonomía epistémica en la conducción de tales modelos de fuerza en las periferias es restringida en el contexto de una geocultura de seguridad por la cual atribuciones específicas, conocimientos y funciones de seguridad se han distribuido de manera desigual en el sistema-mundo moderno.
Forças militares multinacionais do sul global: a isodependência e a busca pela autonomia na geocultura de segurança
Keywords: Multinational military forces; Global south; Isomorphism; Iso-dependence; Epistemic autonomy; Security geo-culture; Forças militares multinacionais; Sul global; Isomorfismo; Geocultura da segurança; Isodependência; Autonomia epistêmica; Fuerzas militares multinacionales; Sur global; Geocultura de seguridad